2011
DOI: 10.1111/j.1466-7657.2011.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and emotional subjective well‐being among Slovak nurses

Abstract: Ď URIŠKOVÁ M. (2012) Job satisfaction and emotional subjective well-being among Slovak nurses. International Nursing Review 59, 94-100Purpose: The purpose of this study is to investigate job satisfaction and emotional subjective well-being and the correlations between these two constructs among Slovak nurses. Design: A cross-sectional survey was used to investigate this relationship among nurses (n = 104) working in seven public hospitals in Slovakia. Methods: Data were collected using a set of questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 34 publications
2
37
0
6
Order By: Relevance
“…When the program was introduced, it was not clear what the roles of the graduate nurses would be and therefore many young people did not embrace it. Nevertheless, Gurkova et al and Wang et al [25,26] found that educational level was not significantly related to job satisfaction. It appears the studies that are conducted in specialty areas like critical care and obstetric units have job satisfaction influenced by ed-ucational level unlike other general areas where education level has minimal impact on job satisfaction.…”
Section: Comparison Between Professional Qualification and Job Satisfmentioning
confidence: 96%
See 1 more Smart Citation
“…When the program was introduced, it was not clear what the roles of the graduate nurses would be and therefore many young people did not embrace it. Nevertheless, Gurkova et al and Wang et al [25,26] found that educational level was not significantly related to job satisfaction. It appears the studies that are conducted in specialty areas like critical care and obstetric units have job satisfaction influenced by ed-ucational level unlike other general areas where education level has minimal impact on job satisfaction.…”
Section: Comparison Between Professional Qualification and Job Satisfmentioning
confidence: 96%
“…[23] Individual characteristics do not determine job satisfaction for nurses at all. [26] It is expected that as nurses age in their career, they are able to make independent decisions, relate well with co-workers especially the physicians, gain expertise in their work and hold higher/managerial positions in their units. Promotions and fringe benefits are frequently based on one's age and amount of experience thus the older nurses might have access to these benefits and therefore perceive their jobs more positively.…”
Section: 6mentioning
confidence: 99%
“…On the contrary, other study has found no correlation between job satisfaction and demographic characteristics [7].…”
Section: Discussionmentioning
confidence: 83%
“…Turnover among nurses is a significant phenomenon that persists in health care organizations [1][2][3][4][5][6][7][8]. It is a major issue both in the developed and the developing countries [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of health care, the well-being of nurses is explained by social interaction phenomena, such as collegial support (Utriainen et al, 2015), feedback (Christiansen, 2008), creating and maintaining interpersonal relationships among nurses (Gurková et al, 2012), and the possibility of having an effect on one's work (Rodwell & Munro, 2013) (see also Utriainen & Kyngäs, 2009). …”
Section: Discussionmentioning
confidence: 99%